Project-based learning through art. A case study of school-university collaboration - Secanell, Irene López; Segura, Francesc Rodrigo (Revista Complutense de Educación, 2023)
Abstract: Introduction. The results and conclusions derived from a case study that investigates the introduction of Project-Based Learning (henceforth ABP) in an educational centre are presented, through projects focused on art as the backbone of didactic proposals that address the curriculum contents in an integrated way so as to achieve meaningful learnings. Method. Research-collaborative action based on the construction of shared knowledge, through researchers and teaching staff working together to design Work Projects in all Infant and Primary education courses. The starting hypothesis is to test the benefits that the development of these PTs generates in the learning community. For this reason, two instruments are used: a quantitative one, a survey conducted by the participating teachers and a qualitative one, and the qualitative analysis of the Learning Diaries carried out by the teachers. Results. The benefits provided by the PTs are described and some difficulties have been identified, to which it is tried to respond. Discussion. At the end of the research, it is revealed that ABP through art-based PTs turns out to be an enriching educational methodology that generates meaningful learnings and contributes to improve educational quality.  Moreover, it advocates expanding research by analyzing similar experiences in other contexts, and encourages the  promotion of  teachers’ research possibilities and the collaboration mechanisms between university and school.
Keywords: project-based learning; art education; collaborative research; case study; infant and primary education